Research data supporting "Shopping Trip Modelling Considering the Impact of Martial Law" - Zhuk, Mykola; Pivtorak, Halyna; Pruskyi, Yevhen; Skyba, Mykola (My University, 2025)
The purchasing behavior of the population affects both passenger and freight traffic in cities. On the contrary, indicators of purchasing behavior are influenced by the characteristics of an individual, as well as external factors. The purpose of the conducted research was to analyse the population's purchasing behavior under martial law conditions. Data was collected by surveying residents of Ukraine's rear regions. Multinomial models of the frequency of purchases and transportation choice during shopping were formed. Martial law conditions and changes in the population size in the rear regions, change the general trends in purchasing behavior. The most visible trends are: a significant share of purchases made online, the popularity of shopping close to home, and the tangible impact of owning a car on the frequency and mode of shopping trips. The results obtained may be helpful in predicting consumer behavior in crisis scenarios.
Keywords: shopping trip; socio-demographic characteristics; multinomial logit model; martial law